x + ay = b ax – by = c solve it by elimination method Question x + ay = b ax – by = c solve it by elimination method in progress 0 Math Autumn 1 month 2021-10-18T22:31:13+00:00 2021-10-18T22:31:13+00:00 2 Answers 0 views 0

## Answers ( )

x + ay = b – – – 1

ax – by = c – – – 2

Divide 2 by a

We get,

x – by/a = c/a – – – 3

Subtract 3 from 1

We get

ay + by/a = b – c

(a^2 y + by) /a = (b-c)

a^2 y + by = a(b-c)

y(a^2 +b) = a(b-c)

y = a(b-c) /(a^2 +b)Put value of y in 1

We get,

x + a*a (b-c) /(a^2 +b) = b

x = b – { a^2 (b-c) /(a^2 +b)}

x = (a^2b + b^2)–a^2(b-c)/(a^2 +b)x=(a^2b+b^2–a^2b–a^2c)/(a^2+b)x=(b^2–a^2c)/(a^2+b)Step-by-step explanation:______________

## I hope the above answer’ll help U mark him as brainliest✌✌